Determinants of women's empowerment in Pakistan: evidence from Demographic and Health Surveys, 2012-13 and 2017-18 - Safdar Abbas; Noman Isaac; Munir Zia; Rubeena Zakar; Florian Fischer (BMC, 2021)
Abstract Background Women's empowerment has always remained a contested issue in the complex socio-demographic and cultural milieu of Pakistani society. Women are ranked lower than men on all vital human development indicators. Therefore, studying various determinants of women's empowerment is urgently needed in the Pakistani context. Methods The study empirically operationalized the concept of women's empowerment and investigated its determinants through representative secondary data taken from the Pakistan Demographic and Health Surveys among women at reproductive age (15-49 years) in 2012-13 (n = 13,558) and 2017-18 (n = 15,068). The study used simple binary logistic and multivariable regression analyses. Results The results of the binary logistic regression highlighted that almost all of the selected demographic, economic, social, and access to information variables were significantly associated with women's empowerment (p < 0.05) in both PDHS datasets. In the multivariable regression analysis, the adjusted odds ratios highlighted that reproductive-age women in higher age groups having children, with a higher level of education and wealth index, involved in skilled work, who were the head of household, and had access to information were reported to be more empowered. Results of the multivariable regression analysis conducted separately for two empowerment indicators (decision-making and ownership) corroborated the findings of the one indicator of women empowerment, except where ownership did not appear to be significantly associated with number of children and sex of household head in both data sets (2012-13 and 2017-18). Conclusions A number of social, economic, demographic, familial, and information-exposure factors determine women's empowerment. The study proposes some evidence-based policy options to improve the status of women in Pakistan.